Business excellence model: an overarching framework for managing and aligning multiple organisational improvement initiatives - Mohammad, Musli; Mann, Robin; Grigg, Nigel; Wagner, Jürgen P (Taylor & Francis, 2011)
Business Excellence Models (BEMs) are used by organisations to assess and improve their work practices and performance. The authors’ research identified that there are currently 94 national Quality/Business Excellence (BE) Awards used in 83 countries. While the use of BEMs is widespread, it was identified that many organisations wanted guidance in terms of which improvement initiatives to implement to assist them on their BE journey. This paper discusses how the BEM can be used as an overarching framework for managing and/or aligning multiple improvement initiatives within the organisation. A new model is developed showing some of the main improvement initiatives that can be adopted towards achieving BE, which are arranged according to the common enabling criteria of BEMs and levels of BE maturity. This proposed model can be used as a pathway/roadmap to BE. In developing this model, a literature review, a document review and several semi-structured interviews were conducted. Sixteen quality and BE experts were interviewed in New Zealand, Singapore, and Malaysia.